Systemically engineering Bacillus amyloliquefaciens for increasing its antifungal activity and green antifungal lipopeptides production - Wang, Susheng; Wang, Rui; Zhao, Xiuyun; Ma, Gaoqiang; Liu, Na; Zheng, Yuqing; Tan, Jun; Qi, Gaofu (Frontiers in Bioengineering and Biotechnology, 2022)
The biosynthesis of antifungal lipopeptides iturin and fengycin has attracted broad interest; however, there is a bottleneck in its low yield in wild strains. Because the key metabolic mechanisms in the lipopeptides synthesis pathway remain unclear, genetic engineering approaches are all ending up with a single or a few gene modifications. The aim of this study is to develop a systematic engineering approach to improve the antifungal activity and biosynthesis of iturin and fengycin in Bacillus amyloliquefaciens. First, blocking the carbon overflow metabolic pathway to increase precursor supply of the branched-chain amino acids by knockout of bdh, disrupting sporulation to extend the stage for producing antifungal lipopeptides by deletion of kinA, blocking of siderophore synthesis to enhance the availability of amino acids and fatty acids by deletion of dhbF, and increasing Spo0A~P by deletion of rapA, could improve the antifungal activity by 24%, 10%, 13% and 18% respectively. Second, the double knockout strain ΔbdhΔkinA, triple knockout strain ΔbdhΔkinAΔdhbF and quadruple knockout strain ΔkinAΔbdhΔdhbFΔrapA could improve the antifungal activity by 38%, 44% and 53% respectively. Finally, overexpression of sfp in ΔkinAΔbdhΔdhbFΔrapA further increased the antifungal activity by 65%. After purifying iturin and fengycin as standards for quantitative analysis of lipopeptides, we found the iturin titer was 17.0 mg/L in the final engineered strain, which was 3.2-fold of the original strain. After fermentation optimization, the titer of iturin and fengycin reached 31.1 mg/L and 175.3 mg/L in flask, and 123.5 mg/L and 1200.8 mg/L in bioreactor. Compared to the original strain, the iturin and fengycin titer in bioreactor increased by 22.8-fold and 15.9-fold in the final engineered strain respectively. This study may pave the way for the commercial production of green antifungal lipopeptides, and is also favorable for understanding the regulatory and biosynthetic mechanism of iturin and fengycin.